P126: Are we transfusing wisely? An analysis of transfusion practices among hemodynamically stable patients with anemia in four hospitals. (15th May 2017) - Wang, A.A.; Lonergan, K.; Wang, D.; Lang, E.
Abstract : Introduction: To help mitigated risks associated with red blood cell transfusions, CWC guidelines recommend practicing restrictively. Transfusion Medicine recommends using a Hgb threshold of 70 g/L, and ordering a single unit at a time (with reassessment after). The purpose of this study is to investigate Emergency Department (ED) compliance with these more restrictive thresholds among hemodynamically stable patients.Methods: A retrospective analysis was performed on data from all emergency visits to 4 adult urban ED sites from July 1 2014 to July 1 2016. We excluded unstable patients (CTAS1, temperature >38°C, HR >100 bpm, RR >20 rpm, systolic BP <90 mmHg, and O2 sat <85%) and certain others (patients without a Hgb level, patients who left without being seen, and orders cancelled via patient discharge). After applying exclusion factors, we examined transfusions ordered. Appropriateness was assessed using the stratified Choosing Wisely Canada Guidelines for Transfusion. As an adjunct, IV iron therapy data was also analyzed for the same period between July 1 2014 and July 1 2016, excluding patients who did not have a Hgb level.Results: We identified 1329 eligible patients (54% female), with a mean age of 68 and average first hemoglobin of 72 g/L. Across all groups, 16% of patients received only 1 unit of blood. 19% of transfused patients had a hemoglobin less than 60 g/L, 45% had a Hgb <70 g/L, 32% had a Hgb 70-80 g/L, 14% had a Hgb 81-90 g/L, and 8% had a Hgb >90 g/L. Over the same two-year period, 178 patients received IV iron. The average Hgb for those patients was 82 g/L.Conclusion: A retrospective analysis documents a significant likelihood of pRBC over-transfusion among Emergency Department physicians and an underutilization of IV iron therapy for certain hemodynamically stable and anemic patients. The development of audit and feedback methods, and creation of a clinical pathway may help address the rate of over-transfusion.